A novel chitosan modified Au@Ag core-shell nanoparticles sensor for naked-eye detection of Hg2+. (22nd November 2019) - Zhang, Jian; Zhu, Ke; Hao, Hequn; Huang, Guangming; Gan, Wei; Wu, Keyue; Zhang, Zhengzhu; Fu, Xucheng
Abstract: In this study, a chitosan-modified Au@Ag core–shell nanoparticles sensor for Hg 2+ detection was prepared by a convenient seed-mediated route. After being adsorbed by the sensor, Hg 2+ ion was reduced to form a mercury shell or amalgam, which changed the dimensional ratio of Au@Ag core–shell nanoparticles. The dimensional ratio changes led the absorption spectra of Au@Ag core–shell nanoparticles be shifted in visible light waveband. It was found that the wavelength shift value of absorption spectra was proportional to the concentration of Hg 2+ over the range from 0.09 to 90 μ mol l −1 . The ion interference study indicated that the sensor exhibited a high selectivity on Hg 2+ by inducing a larger absorption changes over other metal ions in aqueous solution. The chitosan modified Au@Ag core–shell nanoparticles were demonstrated to be a sensitive and selective sensor for Hg 2+ ion detection, which was also proven to be a remarkable facile, rapid, low-cost and sensitive 'naked-eye' chemosensor.